Situational Analysis of Women Empowerment and Gender Equality - Gautam, Susmita (NUTA Journal, 2021)
This study demonstrates the role, opportunity, decision making, responsibility and different issues of gender and the status of the women in the society. Women with comparative to their counter-partners with respect to household works, economic condition, education, health, political and community participation of women with decision-making process. Therefore, the main objective focused on the situation analysis of women empowerment and rural development which has been carried out by using primary and secondary data focused on gender inequality, socio-economic, political, and demographic status. The major findings revealed that the as women are on the process of their empowerment, they need position help and support from their family, society, and country as well. They are lacking various opportunities for income, employment, access to decision making, ownership of property and participation in political parties. Majority of women engage in household work as a result the socio-economic status of women is low. This research focuses to improve the women status in the study area as the government formulates policies and program to integrate the women in development program. Thus, their problems should be addressed properly through empowerment that will lead to economic development in the community as well as the country.